2019
DOI: 10.1164/rccm.201902-0360oc
|View full text |Cite
|
Sign up to set email alerts
|

Rare Protein-Altering Telomere-related Gene Variants in Patients with Chronic Hypersensitivity Pneumonitis

Abstract: Rationale: Rare genetic variants in telomere-related genes have been identified in familial, idiopathic, and rheumatoid arthritis-associated pulmonary fibrosis. Short peripheral blood leukocyte (PBL) telomere length predicts poor outcomes in chronic hypersensitivity pneumonitis (CHP).Objectives: Determine the prevalence and clinical relevance of rare protein-altering variants in telomere-related genes in patients with CHP.Methods: Next-generation sequences from two CHP cohorts were analyzed to identify variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…Other entry mechanisms may also play a role, such as transmembrane protease serine 2 (TMPRSS2), and TMPRSS2 variants and expression have indeed been linked to differences in COVID-19 severity 26 . Susceptibility to the development of post-COVID-19 pulmonary fibrosis could also have a genetic component, as variants in numerous genes or their promotors (such as MUC5B and TERT) have been found to predispose to lung fibrosis, both in the context of idiopathic pulmonary fibrosis and in interstitial fibrosis related to hypersensitivity pneumonitis and collagen vascular disease [27][28][29][30] .…”
Section: Genetics In Covid-19mentioning
confidence: 99%
“…Other entry mechanisms may also play a role, such as transmembrane protease serine 2 (TMPRSS2), and TMPRSS2 variants and expression have indeed been linked to differences in COVID-19 severity 26 . Susceptibility to the development of post-COVID-19 pulmonary fibrosis could also have a genetic component, as variants in numerous genes or their promotors (such as MUC5B and TERT) have been found to predispose to lung fibrosis, both in the context of idiopathic pulmonary fibrosis and in interstitial fibrosis related to hypersensitivity pneumonitis and collagen vascular disease [27][28][29][30] .…”
Section: Genetics In Covid-19mentioning
confidence: 99%
“…The advantage of SKAT analysis is that it overcomes the traditional GWAS’s problem of having low power for rare variants 26 . Rare genetic variants may play key roles in HP development 10 .…”
Section: Discussionmentioning
confidence: 99%
“…After QC, there were 2,353,579 SNPs left. We didn’t exclude rare variants in this study because rare variants were found to be associated with HP significantly 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Sixth, genomic factors such as the MUC5B promoter variant rs35705950 and mutations in the telomerase pathway are associated with an increased risk of the development of pulmonary fibrosis and shortened survival in HP. 6,[45][46][47] Lastly, serum biomarkers are being investigated in CHP, and it is possible that in the future, these will have a role in prognostication. 48 In susceptible subjects, the IA may be causal but not necessarily a risk factor for disease progression.…”
Section: Risk Factors For Disease Progression In Hpmentioning
confidence: 99%